Analisis QFD dalam Upaya Pengembangan Board Game Labirin Matematika sebagai Produk Intelektual UNTIRTA - Khoirunisa, Salsa Nashiroh; Mukhsin, Moh.; Satyanegara, Diqbal (MES Management Journal, 2024)
The research uses the Quality Function Deployment (QFD) approach to study the development of the Mathematical Labyrinth board game application. The problem with this study is the incomplete quality of the Math Labyrinth application, such as unavailable tutorial on the use of the application in video form, a lack of language choices on the application, a design that does not match the color display on the game board, and bugs or errors still found on the app. Quality Function Deployment (QFD) is intended to help solve the problem through user feedback to meet user expectations of the Mathematical Labyrinth application. The method used in this research is quantitative research. The sample population in this study was taken using non probability sampling method with purposive samplings in data collection with 36 respondents. Data analysis techniques using the IBM SPSS Statistic 20 analytical tool. Based on the results of the Quality Function Deployment (QFD) analysis on further product development, the developer team needs to pay attention to priority technical interests such as the entire mode on the game can be played, improve the features of the application more attractive, can train the ability to think and as an alternative to learning, the application works well, improves the ease of use of the app, and improves color combinations that fit the game board.